Perhitungan Biaya Operasional Kendaraan Angkutan Sampah : Studi Kasus : Angkutan Sampah Pasar Rakyat Kota Rengat - Lismawati Lismawati; Sahriyal Sahriyal; Erny Erny (Jurnal Sipil Terapan, 2024)
Daily human activities, either directly or indirectly, produce waste, both in the form of organic waste and non-organic waste. Rengat City People's Market is a place that has quite large potential in producing waste. The increasing activity of the Rengat City People's Market has resulted in an increase in the amount of waste that must be managed. The amount of waste will affect the amount of vehicle operational costs incurred, so it is necessary to calculate vehicle operational costs by considering the traffic conditions involved and also the transportation time. Vehicle operating costs (BOK) are calculated using the PCI (Pacific Consultants International) method. The distance covered by the arm roll vehicle is 32.6 km/day and the travel time is 1.1 hours at a speed of 29.64 km/hour. Based on the results and discussion of the research, it can be concluded that the cost of transporting Rengat City public market waste using arm roll vehicles is IDR. 21,042.20/m3, in a day the total cost of transporting waste is 168,337.57/day.